Kontribusi Motivasi dan Intelligence Quotient (IQ) terhadap Hasil Belajar Biologi Peserta Didik Kelas XI SMAN 6 Padang - Hafizah Suryani; Ardi Ardi (Mathematics Education Study Program, 2025)
This study aims to determine the contribution of learning motivation and Intelligence Quotient (IQ) to the Biology learning outcomes of 11th-grade students at SMAN 6 Padang. Learning motivation is an internal factor that plays a crucial role in enhancing learning effectiveness, while IQ reflects students' cognitive capacity in understanding subject matter. This research employs a descriptive correlational method with a quantitative ex-post-facto approach. The population consists of all 11th-grade science students at SMAN 6 Padang, with samples selected using the proportionate random sampling technique, comprising 25% of students from each class. Data were collected through learning motivation questionnaires, IQ test documentation, and students' Biology learning outcomes. Data analysis was conducted using simple correlation statistical techniques to examine the relationship between the research variables. The findings of this study are expected to provide insights into the extent to which learning motivation and IQ contribute to Biology learning outcomes and serve as a reference for educators in designing more effective teaching strategies to enhance students' academic achievement.This study shows that learning motivation and IQ contribute to the Biology learning outcomes of 11th-grade students at SMAN 6 Padang, with a significant simultaneous relationship (sig. F Change = 0.000; R = 0.794, high correlation). Learning motivation has a greater impact than IQ (Pearson correlation = 0.777, high correlation) as it encourages perseverance, increases study duration, and optimizes concentration. In contrast, IQ has a very low correlation with learning outcomes (Pearson correlation = 0.098) due to other influential factors such as teaching methods and emotional intelligence. Thus, learning motivation plays a more dominant role in determining academic achievement, emphasizing the need for strategies that focus on enhancing students' motivation.